Transportes e metrópoles: Aspectos da integraç\~ao em regi\~oes metropolitanas - Frederico Ferreira Fonseca Pedroso; Vicente Correia Lima Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This article analyze the transport management and the urban mobility in Brazilian metropolitan areas. The transportation and mobility are considered as a public service of common interest on metropolitan arrangements. The paper conducts an analysis of some case studies in order to contribute to the identification of potential failures on planning and operation procedures in some Brazilian Metropolitan areas. The study points out problems of integration and shared management, and notes a conflict of powers between the states, municipalities and the federal government. Finally, it is made three appointments: i) the integrated planning of transport in metropolitan should be a subject of state policy; ii) the lack of integration occurs by the low share of logical processes of planning and operation in the different organizations involved in transport management in a metropolitan area; and iii) the key role of governance.
Keywords: O18; H76; H77; R48; R52; 330; mobility; metropolitan region; metropolitan governance